2007
DOI: 10.1088/1751-8113/40/39/002
|View full text |Cite
|
Sign up to set email alerts
|

Sampling large random knots in a confined space

Abstract: DNA knots formed under extreme conditions of condensation, as in bacteriophage P4, are difficult to analyze experimentally and theoretically. In this paper, we propose to use the uniform random polygon model as a supplementary method to the existing methods for generating random knots in confinement. The uniform random polygon model allows us to sample knots with large crossing numbers and also to generate large diagrammatically prime knot diagrams. We show numerically that uniform random polygons sample knots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Numerical experiments indicate that this probability vanishes faster than expðÀOðnÞÞ (Millett 2000;Arsuaga et al 2007b). This provides evidence for a strong form of the above-mentioned Delbruck-Frisch-Wasserman conjecture in this model.…”
Section: Random Jumpmentioning
confidence: 94%
See 3 more Smart Citations
“…Numerical experiments indicate that this probability vanishes faster than expðÀOðnÞÞ (Millett 2000;Arsuaga et al 2007b). This provides evidence for a strong form of the above-mentioned Delbruck-Frisch-Wasserman conjecture in this model.…”
Section: Random Jumpmentioning
confidence: 94%
“…Experiments with the cube model suggest that the expected knot determinant is x exp n 2 ð Þ. It is proposed in Arsuaga et al (2007b) that most knots in this model are prime. It was suggested (Thurston 2011) that the expected crossing number in the spherical case is Hðn 2 Þ.…”
Section: Random Jumpmentioning
confidence: 99%
See 2 more Smart Citations
“…The radius of gyration estimates the size of a molecule and can be experimentally measured by standard sedimentation assays. In [18] it was found that the squared radius of gyration of a polygonal molecule increases as 1 12 n 2ν with ν = 0.5. Our result is in excellent agreement with that presented in [18] as shown in Figure 9.…”
Section: • Distributionsmentioning
confidence: 99%